Respon Petani Terhadap Teknologi Pembuatan Pakan Unggas dari Limbah Mete di Desa Alebo Kecamatan Konda Kabupaten Konawe Selatan - Agustina, Dian (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2011)
This research was aimed to study the response of poultryman on made fowl of fooder from mete of waste product. The sample size on this research has taken by Sensus of Method that is used the all number of population as the sample about 15 people. The results of data analysis indicates that all poultryman has given positive response on made fowl of fooder of technology, likely most 15 people (100%) declare that the material is simple, most 10 people have declared that the material process is easy, and the last 15 people (100 %) has declared that knowledge regarded material of process is most utility. Therefore, disseminating regarded technology of the fooder process made is more significant to do.